CLINICAL PSYCHIATRIC INTERVIEW (LECTURE) - V. G. KOSENKO; G. T. KRASILNIKOV; M. I. AGEEV; L. M. SHULKIN; N. A. KOSENKO; YU. V. GRIDINA; YA. A. ZAKHAROVA-MAKAGON; N. V. ISAEVA (Кубанский научный медицинский вестник, 2018)
Aim. To reflect the theoretical foundations and create a minimum set of practical skills of diagnostic and treatment interviewing in psychiatry.Materials and methods. To achieve this goal a thematic selection of scientific literature sources of both classical and modern domestic and foreign authors was carried out. In addition, the authors focused on the rich personal experience of interviewing, which allowed choosing and describing the most effective, practically significant methods and methods of clinical diagnosis in psychiatry in the form of psychiatric interviewing.Results. The factors that determine the nature and content of the interview: place, time, participants of the interview – doctor and patient have been described and analyzed. The analytical description of the main psychotechnologies which are used by the psychiatrist (psychotherapist) in the course of interview is given: establishment of contact, technology of hearing of and listening to the patient, technology of asking questions, technology of a pause and silence, technology of tactile contact, technology of using humour, advice, recommendation, interpretation, technology of finishing the interview and its structuring.Conclusion. Clinical interview is the main diagnostic and psychotherapeutic tool of a psychiatrist, and especially of a psychotherapist. The diagnostic effectiveness of a psychiatric interview is determined by the extent to which the information obtained in the course of it is structured into a diagnostic concept, the therapeutic effectiveness is determined by the extent to which the patient accepts the concept of understanding by the doctor of his painful condition (achieved compliance).